Іntegration of university education teacher of Ukraine into the European educational space - Желан, А. В. (Educational Dimension, 2012)
Dgelan A. Іntegration of university education teacher of Ukraine into the European educational space. The article deals with the current trends of integration of higher pedagogical education in Ukraine, the content of university teacher training, the creation of a system of teacher training, the learning process in higher educational establishments.